CoxFeyN nanoparticles decorated on graphene sheets as high-performance electrocatalysts for the oxygen evolution reaction. Issue 20 (7th May 2019) - Liu, Haixia; Lu, Xinyao; Hu, Yi; Chen, Renpeng; Zhao, Peiyang; Wang, Lei; Zhu, Guoyin; Ma, Lianbo; Jin, Zhong
Abstract : The Co x Fe y N nanoparticles with adjustable Co/Fe atomic ratios loading on graphene sheets exhibit ultrahigh activity and stability for oxygen evolution reaction in alkaline solution. Abstract : Exploring highly efficient non-noble metal based catalysts for the oxygen evolution reaction (OER) is of great importance for the development of renewable energy conversion technologies, such as water-splitting devices and rechargeable metal–air batteries. Co-based electrocatalysts have been regarded as a class of highly active and earth-abundant catalysts for the OER, but most of them are semiconductors or insulators that may limit the OER efficiency. Herein, we report the facile preparation of Co x Fe y N nanoparticles uniformly loaded on graphene sheets (Co x Fe y N/graphene) with amazing OER activity and stability, attributed to the intrinsic metallic characteristics. Through partial Fe heteroatom substitution in Co4 N lattices, the disorder of the crystalline structure could be increased, thus forming a more favorable electronic structure for the catalysis of the OER. By adjusting the atomic ratios of Co/Fe elements, we found that the Co3 Fe1 N/graphene catalyst exhibited the highest activity for the OER under alkaline conditions among the Co x Fe y N/graphene samples, showing the lowest overpotential of 266 mV at 10 mA cm −2, the highest current density of 105.83 mA cm −2 at 1.53 V, and the lowest Tafel slope of 32 mV dec −1 . Moreover, the freestanding electrodes of Co x Fe y N/graphene catalysts loaded on carbon paper (CP) also exhibited excellent long-term stability for the OER, and the overpotentials only slightly increased after continuously testing for 16 h at 10 mA cm −2 . Among all the Co x Fe y N/graphene/CP samples, the Co3 Fe1 N/graphene/CP sample also displayed the best long-term stability and the lowest overpotential (270 mV) after 16 h. This work presents the great potential of Co x Fe y N/graphene catalysts as promising non-noble metal electrocatalysts for the OER for application in clean energy conversion devices.